Pioglitazone enhances the blood pressure-lowering effect of losartan via synergistic attenuation of angiotensin II-induced vasoconstriction - Xiang Kong (Journal of the Renin-Angiotensin-Aldosterone System, 2014)
Introduction: This study was designed to investigate the underlying mechanisms of synergistic antihypertensive effect produced by combination therapy of losartan and pioglitazone in metabolic syndrome (MS) rats. Materials and methods: An MS model was induced by feeding rats a high-fat, high-sodium diet and 20% sucrose solution. Losartan (20 mg/kg/day), pioglitazone (10 mg/kg/day), and their combination were orally administered for eight consecutive weeks. Systolic blood pressure (SBP) and mean arterial pressure (MAP) were measured using the tail-cuff method and carotid arterial catheterization, respectively. The aortas were isolated and in vitro vascular reactivity studies were performed. The protein expression of angiotensin type 1 receptor (AT 1 ), endothelial nitric oxide synthase (eNOS), phosphorylated eNOS and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase subunit p47 phox , level of nitrotyrosine as well as activity of eNOS and NADPH oxidase in aortas of MS rats were detected. Results: After eight weeks of treatment, the SBP and MAP in the losartan (115 ± 5 and 106 ± 6 mmHg), pioglitazone (130 ± 6 and 118 ± 6 mmHg), and combination therapy (105 ± 6 and 98 ± 5 mmHg) groups were lower than those in the model group (150 ± 8 and 136 ± 9 mmHg). Combination therapy of losartan and pioglitazone reduced BP more than either monotherapy, and showed additive effects on improving endothelial dysfunction and abolishing the increased vascular responsiveness to angiotensin II. These synergistic effects were associated with further reductions in protein expression of p47 phox and AT 1 , NADPH oxidase activity, and nitrotyrosine level. Conclusions: Our data indicate that combined treatment exerts more beneficial effects on lowering BP and improving vascular lesions.